(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article deals with the national composition, number and other characteristics of the population of Zarafshan district, which was a special administrative-territorial unit of the Governor-Generalship of Turkestan. To shed light on the problem, a historicalsource analysis of written sources, archival materials, research, and historical literature involved in the research process was conducted.